War ethics in armed conflicts under international humanitarian law and islamic perspective / Muhammad Syahlan Shafie …[et al.] - Shafie, Muhammad Syahlan; Mohd Arif, Mohd Izzat Amsyar; Adenan, Faezy; Jamal, Ikmal Hafiz (Universiti Teknologi MARA, 2021)
This study aims to examine the war ethics in armed conflicts under international humanitarian law and Islamic perspective. To achieve the objective of the study, semi-structured interviews were carried out with two legal officers in the Royal Malaysian Air Force (RMAF). The legal qualitative research was conducted by adopting a document analysis method to strengthen the findings. The study shows that there are similarities in war ethics between International Humanitarian Law (IHL) and the teachings of Islam. Both bring a war ethic that is not aimed for devastation and victory,but rather to protect oneself and the nation against the threat of the enemy.However, if human beings or the military do not follow and obey what has been outlined in the IHL and the guidance of war in Islam, this ethics will not be useful. If these war ethics are adequately practiced, then the world will not suffer destruction and prolonged war. Therefore, this study is very significant to bring a message of peace and harmony to the world, especially to appreciate the ethics of war in IHL and Islam to live in peace and tranquility in the future.